REALISATION DES APPROCHES STYLISTIQUE, LINGUISTIQUE ET INTERCULTURELLE DANS L’ANALYSE COMPLEXE DES OEUVRES LITTEEAIRES - Беденко, Д.В.; Оспанова, А.С. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2016)
The article discusses the features of stylistic, linguistic and intercultural approaches to the analysis of a literary text, it also treats the question of comprehensive intercultural competence. Furthermore, it contains the overview of different French and Swiss authors' theories, dedicated to the comprehensive text analysis. The role of style and intercultural competence for the formation of linguistic competences is shown here. The article includes a practical use of the comprehensive text analysis.
Keywords: modern technologies of the literary text comprehensive analysis; linguistics; stylistics; stylistic means; history of the French literature; intercultural competences; psycholinguistics